The Exploitation of Artificial Intelligence in Digital Artworks: The Challenges of Copyright Recognition in the Post-Human Era - Sjofjan, Lindryani; Nugraha, Roby Satya (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The purpose of this research is to provide an in-depth explanation that the development of artificial intelligence technology (AI) has revolutionized the process of creating digital artworks. AI is now able to produce works that resemble, even surpass, human creations. This phenomenon poses significant legal challenges, especially related to copyright recognition. In the context of the post-human era, where the boundaries between humans and machines are increasingly blurred, the fundamental question arises as to who deserves to be called a creator: human, machine, or both. This article examines the current copyright legal framework and examines the extent to which legal norms are able to accommodate the existence of AI as a creative entity. The method used is a normative juridical approach with analysis of national and international regulations, as well as case studies of a number of AI-based digital artworks. The findings show that the current legal system is not fully ready to regulate the protection of copyrights involving AI autonomously. Therefore, regulatory updates are needed that are responsive to technological advances and still ensure justice for creative actors in the digital era.